Sin Taxes' Impact On Consumption, Revenue, And Health: A Systematic Review In The Philippines. - Limos, Shaniah (Community Development Journal, 2025)
The Philippines implemented Republic Act 10351, also known as the Sin Tax Reform Act of 2012 to reform the excise tax on potentially harmful goods such as tobacco, alcohol, sugar-sweetened beverages (SSBs), etc. This paper aims to assess and review the impact of the Sin Tax Law (STL) in the Philippines and to contribute to the analysis of its effects on these three endpoints: Consumption, the government's revenue generation, and overall public health. This research employs a systematic literature review (SLR) to assess the impact of the STL in the Philippines. Relevant literature were gathered from databases such as PubMed, Directory of Open Access Journals (DOAJ), Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Tobacco Induced Diseases (TID). The PRISMA Model was utilized to screen and select appropriate sources. Findings revealed that STL’s impact was most apparent in the initial years following its implementation. The consumption of sin goods decreased, but a study on the elasticity of demand for tobacco showed that it is inelastic. The tax revenue collected by the government significantly increased, which is then allocated to health care programs. Additionally, illnesses and deaths caused by tobacco use also declined. However, people will always find a roundabout to avoid being affected by this law by purchasing from illicit markets that arose and thrived a few years after STL implementation. Hence, continuous study is needed to assess STL further and ensure that it still serves its purpose and fulfills its objectives. Ongoing policy adjustments may be required to address market behavior and prevent exploitation of legal loopholes that compromise public health and revenue outcomes.